2013
DOI: 10.1111/aspp.12017
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Economic Development on Political Development in Authoritarian States: An Initial Study of Interest in Politics Across Social Classes inChina

Abstract: Over the past several decades, modernization theory has offered much insight into the conditions necessary for a democratic transition. Proponents of this theory suggest that a link exists between economic development and a democratic transition. Economic development leads to a stronger middle class that develops a greater interest in politics and places demands upon the government, which may lead to regime concessions and an eventual democratic transition. Emerging research, however, suggests there is a link … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 22 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…1 As indicated in Table 1, Owen [14] found that political interest was not differentiated across the middle and working classes. In other words, all of the social class measures were statistically insignificant across 24 regions of China.…”
Section: Political Interest In Chinamentioning
confidence: 94%
See 4 more Smart Citations
“…1 As indicated in Table 1, Owen [14] found that political interest was not differentiated across the middle and working classes. In other words, all of the social class measures were statistically insignificant across 24 regions of China.…”
Section: Political Interest In Chinamentioning
confidence: 94%
“…In other words, all of the social class measures were statistically insignificant across 24 regions of China. Owen [14] suggested that the working class hypothesis offered by Rueschemeyer et al [18] sufficiently explained the absence of statistical significance on the middle class measures. Moreover, the economic and political conditions in China may no longer be conducive for mass organization, resulting in a working class that is now more fragmented, internalized, and localized than ever before, suggested Owen [14].…”
Section: Political Interest In Chinamentioning
confidence: 99%
See 3 more Smart Citations